2016
DOI: 10.1039/c6ra02207c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of BaSnO3 and Ba0.96La0.04SnO3 by reactive core–shell precursor: formation process, CO sensitivity, electronic and optical properties analysis

Abstract: A facile method for preparing pure and La doped BaSnO3 by reactive core–shell precursor was proposed and clear evidence of conduction band filling in La doped BaSnO3 was presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…During the regeneration process, the oxide layer can deliver oxygen to inner Fe 0 coupled with the oxidation of Fe 0 species in oxidizing atmosphere, while the confined Fe species in the core area of particle re-enter the perovskite lattice. Various studies on the kinetics of solid reaction showed that the fabrication of core-shell structure could accelerate the formation of perovskite, since the contact area of the reactants is normally larger while the ion diffusion distance is decreased 47,48 . For LaFeO 3 , La 2 O 3 phase appeared obviously after 20 cycles as shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During the regeneration process, the oxide layer can deliver oxygen to inner Fe 0 coupled with the oxidation of Fe 0 species in oxidizing atmosphere, while the confined Fe species in the core area of particle re-enter the perovskite lattice. Various studies on the kinetics of solid reaction showed that the fabrication of core-shell structure could accelerate the formation of perovskite, since the contact area of the reactants is normally larger while the ion diffusion distance is decreased 47,48 . For LaFeO 3 , La 2 O 3 phase appeared obviously after 20 cycles as shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The d -spacing's equal to 0.328 nm, 0.172 nm, and 0.281 nm correspond to the (110), (113), and (110) crystal planes of SnO 2 , BaCO 3 , and BaSnO 3 , respectively. 29 …”
Section: Resultsmentioning
confidence: 99%
“…This is likely to change the electrical performance due to contrasting properties depending upon the type of forming system and the mixed solid solution. 16 It includes phase transition (ferro–paraelectric), dielectric and alternates (increase/decrease) in resistance with temperature and frequency. 17 The obtained modification makes this material suitable and useful for many industrial applications.…”
Section: Introductionmentioning
confidence: 99%